Double-headed nanosystems for oral drug delivery. Issue 33 (14th March 2019) - Kaur, G.; Arora, M.; Ganugula, R.; Kumar, M. N. V. Ravi
Abstract : We demonstrate a novel strategy to engineer double-headed nanosystems by chemical modification of the carboxyl terminal polyester with a linker that offers tripodal arrangement of ligands on the particle surfaces. Abstract : We demonstrate a novel strategy to engineer double-headed nanosystems by chemical modification of the carboxyl terminal polyester with a linker that offers tripodal arrangement of ligands on the particle surfaces. The in vivo results suggest that the bioavailability of encapsulated curcumin is proportional to the ligand density rendered by double-headed nanosystems.